Avaliação da expressão dos microRNAs e níveis séricos de CK-MB, Troponina I e Lactato como marcadores de eventos perioperatórios em cirurgia cardíaca - Piantá, Ricardo Medeiros (2018)
Cardiovascular diseases are one of the most prevalent diseases worldwide and the main cause of mortality in Brazil. They are responsible for 34% of the deaths in America. The most prevalent cardiovascular disorder are ischemic heart disease, stroke, cardiac insufficiency and arterial systemic hypertension. The risk stratification for patients submitted to cardiac surgery comprehends pre operatory risks, mainly. However, during intraoperative period several factors, including surgical technique, myocardial protection and cardiopulmonary bypass may interfere in post-operative results. Thus, intraoperative monitoring and early intervention may improve cardiac surgery outcomes. The increase of serum biomarkers levels indicates myocardial lesion and even necrosis in subjects submitted to cardiac surgery. The biomarker concentration may be related to an adverse outcome. Blood level measures of lactate can also be used as a marker to assess adequate tissue perfusion; providing the magnitude of anaerobic metabolism and tissue oxygenation deficiency. The microRNAs (miRNAs) are part of a non-coding endogenous class of RNAs that act as potent post-transcriptional regulators of gene expression. Moreover, miRNAs present characteristics that make them good biomarkers with high levels of sensibility and specificity allowing early detection of pathological states. In addition, they also change in accordance to the disease course and have a long half-life in the sample enabling an easy laboratory detection. This study identified the profile of cardiac biomarkers such as CK-MB, troponin I and lactate in 115 patients submitted to cardiac surgery and its correlation with the outcome. It was analyzed the expression of miRNAs 1, 133a and 499 expression in 24 individuals as well as the correlation between the biochemical and molecular biomarkers. A correlation of miRNA-1 with troponin I (r = 0.4893, P = 0.0025) and lactate (r = 0.5689, P = 0.0002) was found, which pointed to the first evidence that a miRNA is related to the state of hypoperfusion and tissue oxygenation, monitored by serum lactate. These data will allow the potential of these complex nucleotides to be explored in future studies for the diagnosis, monitoring and therapy of the most diverse pathologies and cardiac surgeries.